3P Strategy in Verrel Bramasta's Political Marketing in the 2024 Legislative Election: Instagram Social Media Content Analysis - Muhammad Alif Ariga; Asri Nur Mahdia Devi; Bintan Auliya Qurrota A’yun; Syarifah Nur Aini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This research is based on the phenomenon that occurred in the 2024 general election, where political marketing has become a common instrument used by candidates or political parties. This is done to approach the public to gain support that allows them to win political office. This research aims to analyze the 3P (Push, Pull, Pass) strategy used by Verrel Bramasta in his political campaign in the 2024 legislative elections, focusing on the Instagram social media platform. In the context of political marketing, social media has become an important tool to gain public support and build a candidate's image. This research adopts a qualitative approach with the data collection technique of documentation from Verrel Bramasta's Instagram posts during a certain campaign period. The content analysis method is used to decipher the meaning of his political campaign content by paying attention to the use of the 3P strategy and its impact on public perception and voter participation. The results of this study show that the use of social media can strengthen the image and gain support from voters, which increases the chances of winning.